Exploring the potential of human bone and teeth collagen from Prehistoric Cyprus for isotopic analysis. (December 2018) - Goude, Gwenaëlle; Clarke, Joanne; Webb, Jennifer M.; Frankel, David; Georgiou, Giorgos; Herrscher, Estelle; Lorentz, Kirsi O.
Abstract: This pilot study attempts to document the potential of Prehistoric human bone and teeth collagen from Cyprus (9th-2nd mill. BC), for isotopic analysis and palaeodietary reconstruction. We sampled archaeological human skeletons and some faunal remains coming from six sites located in different locations, with different burial modes. The analysis of carbon and nitrogen elemental compositions and stable isotope ratios (δ 13 C, δ 15 N), indicate an extremely poor preservation of collagen, probably in relationship with burying conditions. Although very few individuals were successfully analysed, stable isotope data from this study allow a discussion on different protein food resources intake by humans in comparison with some other published data in the Near East (Greece, Cyprus, Turkey) from the Neolithic to the Bronze Age. These diachronic data provide documentations for future studies, including palaeodietary and environmental field research. Highlights: Bone and teeth collagen extraction was performed on prehistoric Cypriot human remains Elemental compositions and stable isotope ratios (C, N), indicate an extremely poor preservation of collagen Few individuals were successfully analyzed and data allow a discussion on different protein food resources intake Our results were compared to published data in the Near East (Greece, Cyprus, Turkey) from the Neolithic to the Bronze Age Dietary shift and legumes consumption are carefully discussed